On the convergence of the sums of multidimensional stochastic step processes of random number to generalized Poisson processes - Banys, R. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Р. Т. Банис. О сходимости сумм случайного числа многомерных ступенчатых случайных процессов к обобщенным пуассоновскимR. Banys. Apie atsitiktinio skaičiaus daugiamačių laiptuotų atsitiktinių procesų sumų konvergenciją į apibendrintus Puasono procesus